Evaluations for sustainable forest management: towards an adaptive standard for the evaluation of the ecological sustainability of forest management in Costa Rica - McGinley, Kathleen; Finegan, Bryan (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
The evaluation of the sustainability of forest management is an integral measure in the maintenance of production, and the ecological and socioeconomic functions of forest systems and should consider both the fulfillment of sound forest practices as well as the impacts and result of forest management, providing key information for the identification of aspects of negative impact that can be improved or modified within a system of adaptive management. The research presented here was carried out with the general objectives of contributing to the definition of sustainable forest management in the region of Central America, determining guidelines for the ecological sustainability of forest management that include elements necessary for adaptive management and developing. Throughout the process of testing and validation there was a clear indication of the need for a realistic distribution of institutional responsibilities for implementation which should include important actors such as forest operators, forest managers, regents, evaluators, research institutions and the Costa Rican State Forestry Administration.